FISHERY RESOURCES IN THE WEST COAST OF ACEH AFTER TSUNAMI: RESULTS OF THE BOTTOM TRAWL SURVEYS - Wijopriono Wijopriono; Wedjatmiko Wedjatmiko; Suprapto Suprapto (Indonesian Fisheries Research Journal, 2007)
Investigation on fishery resources in the west coast of Aceh Province was carried out during July until August 2005 and August until September 2006. One of the objectives of the investigation was to determine the state of demersai stock after the area severely hit by tsunami in December 2004.